Urban water security in South Asia: Crucial policy lessons from the Nepalese town of Bidur. Issue 2 (10th December 2020) - Ojha, Hemant; Neupane, Kaustuv R.; Khatri, Dil; Devkota, Kamal; Maskey, Gyanu; Dahal, Ngamindra; Joshi, Tikeshwari; Kovacs, Eszter K.
Abstract: The rapidly urbanizing and highly populated South Asian region is facing a water crisis. As a key response, large centralized water systems are being put in place, replacing small and community‐based systems. In this discussion note, we present the case of Nepal's town of Bidur to show that Himalayan South Asian towns cannot ensure water supply by neglecting community‐based and small‐scale water supply systems. Using insights from qualitative and quantitative data collected during 2014–2019, we argue that decentralized and community‐based urban water systems are more resilient than large ones during disasters. Our argument is based on the analysis of Bidur's response to the 2015 earthquake as well as the COVID‐19 pandemic. We show that a mixed approach of large and small water supply schemes provides a promising solution to water insecurity in the South Asian towns. This approach can be realized by promoting diversity of water management strategies and creating research‐informed planning and discussion forums at the community and municipality levels. We also recommend municipalities to formulate a comprehensive water security strategy, considering the current and future scenarios of water demand and supply. 摘要: 快速城市化和人口稠密的南亚地区正面临水危机。作为关键响应, 大型集中化水系统正在建立, 代替小型和由社区管理的水系统。本篇探讨文中, 我们以尼泊尔比德尔 (Bidur) 镇为例, 证明了喜马拉雅南亚城镇无法在忽视基于社区和小型水供应系统的情况下确保水供应。通过使用2014年至2019年间收集的定性和定量数据, 我们论证认为, 灾害期间, 权力下放和基于社区的城市水系统的复原力比大型水系统更强。我们的论证分析了比德尔镇对2015年地震灾害和对新冠肺炎 (COVID‐19) 大流行所作的响应。我们表明, 大型和小型水供应计划的混合方法能为南亚城镇的水资源不安全性提供一个有希望的解决方案。通过推动水管理策略的多样性、并从社区和市政层面创造基于研究的规划和论坛, 则能实现该混合方法。我们还建议市政制定一个全面的水安全策略, 将当前和未来的水需求和供应情况考虑在内。 Resumen: La región de Asia meridional que se urbaniza rápidamente y está muy poblada se enfrenta a una crisis del agua. Como respuesta clave, se están instalando grandes sistemas de agua centralizados, que reemplazan los sistemas pequeños y comunitarios. En esta nota de debate, presentamos el caso de la ciudad de Bidur en Nepal para demostrar que las ciudades del Himalaya del sur de Asia no pueden garantizar el suministro de agua descuidando los sistemas de suministro de agua de base comunitaria y de pequeña escala. Utilizando conocimientos de datos cualitativos y cuantitativos recopilados durante 2014–2019, argumentamos que los sistemas de agua urbanos descentralizados y comunitarios son más resistentes que los grandes durante los desastres. Nuestro argumento se basa en el análisis de la respuesta de Bidur al terremoto de 2015 y a la pandemia de COVID‐19. Mostramos que un enfoque mixto de esquemas de suministro de agua grandes y pequeños proporciona una solución prometedora a la inseguridad hídrica en las ciudades del sur de Asia. Este enfoque se puede realizar mediante la promoción de la diversidad de estrategias de gestión del agua y la creación de foros de discusión y planificación informados por la investigación a nivel comunitario y municipal. También recomendamos a los municipios que formulen una estrategia integral de seguridad hídrica, considerando los escenarios actuales y futuros de demanda y suministro de agua.